Text of postcard from James Connolly to William O'Brien requesting that an account of the Labour Party congress be sent to 'Forward' and to Connolly, - Connolly, James, 1868-1916 (1911)
Connolly mentions a statement from "McD of Belfast" [Danny McDevitt?] that [James] Larkin "defeated the motion by his support", and again requests a quotation from Dan[iel O'Brien] [by [August] Bebel, see MS 13,908/1/46)].